Adult sea lamprey respond to induced turbulence in a low current system. Issue 1 (2nd January 2021) - Zielinski, D. P.; Miehls, S.; Burns, G.; Coutant, C.
Abstract: Manipulation of water velocities and turbulence using pumps, propellers, or jets is a promising alternative to physical water control structures to guide fish towards traps or fishways. Sea lamprey ( Petromyzon marinus ) are a species of concern in much of their native and invasive ranges, and their improved guidance could benefit management actions for both conservation and control. The flow velocity enhancement system (FVES), an emergent technology that uses a Venturi pump to generate a plume of turbulence, has shown promise guiding downstream migrating fish in slow-moving or static water conditions formed by large reservoirs, but is untested for guidance of upstream swimming fish in low current environments. The FVES had minimal impact on depth averaged velocity profiles, but produced elevated levels of turbulence. Changes in spatial distribution and number of turns suggest sea lamprey detect and are mildly attracted to turbulence induced by the FVES. These results demonstrate the potential of induced turbulence as a guidance mechanism for upstream migrating sea lamprey, but more extensive testing is needed to show the full utility of this approach.